A fluorescent cross-linked supramolecular network formed by orthogonal metal-coordination and host–guest interactions for multiple ratiometric sensing. Issue 4 (9th January 2018) - Xu, Luonan; Chen, Dong; Zhang, Qian; He, Tian; Lu, Chenjie; Shen, Xi; Tang, Danting; Qiu, Huayu; Zhang, Mingming; Yin, Shouchun
Abstract : A supramolecular network can be used for the ratiometric sensing of pH, cyclen and Cl − due to the incorporation of two fluorophores and two non-covalent interactions. Abstract : A cross-linked supramolecular network was prepared by the orthogonal self-assembly of metal-coordination and host–guest interactions. Due to the incorporation of two fluorophores, coumarin and tetraphenylethene, into the network as well as the abundant stimuli-responsiveness of the two non-covalent interactions, it can be used for the ratiometric sensing of pH, cyclen and Cl − .